2013
DOI: 10.1063/1.4819491
|View full text |Cite
|
Sign up to set email alerts
|

Optical critical coupling into highly confining metal-insulator-metal resonators

Abstract: Articles you may be interested inMid-infrared intersubband polaritons in dispersive metal-insulator-metal resonators Appl. Phys. Lett. 105, 081105 (2014); 10.1063/1.4893730An electrically driven terahertz metamaterial diffractive modulator with more than 20 dB of dynamic range Appl. Phys. Lett.Optical bistability based on Bragg grating resonators in metal-insulator-metal plasmonic waveguides AIP Advances 3, 012106 (2013); 10.1063/1.4775353A weakly coupled semiconductor superlattice as a potential for a radio f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 28 publications
2
34
0
Order By: Relevance
“…Most importantly, it is possible to estimate the system absorption as A = 1 -R -T: 24% and 28% of the light is absorbed respectively by the upper and lower polaritonic resonances. This value is in line with what is achieved with systems with a metallic back-plane when not in critical coupling [36], and it can be improved with judicious sample design.…”
Section: Cryogenic Performance and Device-oriented Perspectivessupporting
confidence: 84%
See 1 more Smart Citation
“…Most importantly, it is possible to estimate the system absorption as A = 1 -R -T: 24% and 28% of the light is absorbed respectively by the upper and lower polaritonic resonances. This value is in line with what is achieved with systems with a metallic back-plane when not in critical coupling [36], and it can be improved with judicious sample design.…”
Section: Cryogenic Performance and Device-oriented Perspectivessupporting
confidence: 84%
“…The use of judiciously doped semiconductor QWs led to the observation of strong light-matter coupling between an ISB transition and the resonator photonic mode, at 300 K and at 78 K. We have also shown that placing the coupler grating on the air/active region boundary or burying it on the active region/CaF2 boundary leads to equivalent results. In the field of polaritonics such a two port system [27,36], with a near-IR transparent substrate and flexibility in radiation coupling, can represent a precious asset to study the temporal construction of polaritonic states [24] and possibly Casimir radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Its electromagnetic coupling to the external world is described by a radiative damping rate γ r , while the resonator losses are lumped into a non-radiative rate γ nr . When the two damping rates are matched (γ r = γ nr ), all the incoming photons are coupled into the resonant photonic mode, a situation known as critical coupling 24,27 . Interestingly, this general concept also holds for the regime of strong coupling, as developed in Ref.…”
mentioning
confidence: 99%
“…For QWIPs, the matching of radiative-and absorption-induced decay rates is a key issue (critical coupling), and this tuning mechanism is complementary to that reported in Ref. 25. For GMRFs, a fully-contrasted, isolated transmission feature of tunable linewidth is the essence of the device.…”
mentioning
confidence: 56%